2005
DOI: 10.1007/bf03027390
|View full text |Cite
|
Sign up to set email alerts
|

Dobutamine stress tetrofosmin SPECT; evaluation of short rest-stress protocol and head to head comparison with MIBI in detection of coronary artery disease

Abstract: MIBI and TF showed similar perfusion defects and good segmental correlation during dobutamine stress with the same quality images. Both radiopharmaceuticals may be acceptable with this imaging protocol. Besides this, TF study showed better reversibility degree (55%) in a shorter time when compared to MIBI study (25%) in perfusion defects (especially in segments with severely decreased perfusion or no uptake).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
(5 reference statements)
0
4
0
Order By: Relevance
“…A small study by Turgut et al in 2005 with 19 patients employed a one-day rest-dobutamine stress performed with both sestamibi and tetrofosmin one week apart. 23 This was one of the few studies to image with tetrofosmin and sestamibi in the same patient. The injection to image acquisition time for sestamibi was 60 minutes for rest and stress and 30 minutes for tetrofosmin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A small study by Turgut et al in 2005 with 19 patients employed a one-day rest-dobutamine stress performed with both sestamibi and tetrofosmin one week apart. 23 This was one of the few studies to image with tetrofosmin and sestamibi in the same patient. The injection to image acquisition time for sestamibi was 60 minutes for rest and stress and 30 minutes for tetrofosmin.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies reviewed found no significant difference between heart and extra-cardiac ratios between sestamibi and tetrofosmin despite using significantly earlier starting times with tetrofosmin. In the only study assessing the two tracers in the same patient, Turgut et al, 23 an evaluation of 19 patients found no difference in heart to extra-cardiac ratios despite a 30 minute shorter imaging delay for tetrofosmin. Meta-analysis could not be accurately performed on these groups of articles due to the heterogenous nature of the studies, variability in methodology, and non-uniform endpoints.…”
Section: Discussionmentioning
confidence: 99%
“…A perfusion score of 0 indicates that there is no perfusion defect, 1 indicates minimally reduced perfusion, 2 indicates moderately reduced perfusion, 3 indicates severely reduced perfusion and 4 indicates that there is no perfusion. In this scoring system, a score of 0-1 was considered as normal perfusion and 2-4 was considered as abnormal perfusion 4,8,9 . According to the arterial sites, apical anterior, apical inferior, septal, anteroseptal, anterior and anterolateral segments (segment 1, 2, …”
Section: Methodsmentioning
confidence: 99%
“…A perfusion score of 0 indicates that there is no perfusion defect, 1 indicates minimally reduced perfusion, 2 indicates moderately reduced perfusion, 3 indicates severely reduced perfusion and 4 indicates that there is no perfusion. In this scoring system, a score of 0-1 was considered as normal perfusion and 2-4 was considered as abnormal perfusion 4,8,9 . According to the arterial sites, apical anterior, apical inferior, septal, anteroseptal, anterior and anterolateral segments (segment 1, 2, 7, 8, 9, 10, 15, 16, 17, 18, 23, 24, 25 and 26) represent LAD; lateral and inferolateral segments (segment 3, 4, 11, 12, 19 and 20) represent lateral circumflex artery (LCx); and inferior and inferoseptal segments (segment 5, 6, 13, 14, 21 and 22) represent right coronary artery (RCA) 10 .…”
Section: Methodsmentioning
confidence: 99%